E-MODULE OF CONTEXTUAL BASED CHEMISTRY IN INCREASING LEARNING ACTIVITY ON HYDROCARBON COMPOUND MATERIAL - Siregar, Tiurlina; Semuel Franklyn Yawan; Samosir, Rendra Christian (Jurnal Ilmu Pendidikan Indonesia, 2025)
Abstract: This study aims to find out how to make contextually based chemistry e-modules, developcontextually based chemistry e-modules, feasibility of contextually based chemistry e-modules, increaselearning activity, increase learning interest and learning outcomes of class XI IPA students using e-modulescontextual based chemistry on the material of hydrocarbon compounds. The research method used isResearch and Development (R&D). The research was conducted in class XI IPA of SMA Negeri Samberwith a total of 22 students. The results of the study show that: Assessment of student learning activeness inlesson plan 1 to lesson plan 3 obtains a percentage of 82% in the active category.Keywords: Chemistry E-module, Contextual, Active learning, Hydrocarbon Compounds.